2012
DOI: 10.1055/s-0031-1300590
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of erdosteine metabolite I against hydrogen peroxide-induced oxidative DNA-damage in lung epithelial cells

Abstract: It has been shown that the mucolytic agent erdosteine (N-carboxymethylthio-acetyl-homocysteine thiolactone, CAS 84611-23-4) has anti-inflammatory and anti-oxidant properties, and an active metabolite I (MET I) containing pharmacologically active sulphydryl group has been found to have a free radical scavenging activity. The aim of this study was to assess the ability of erdosteine metabolite I to protect A549 human lung adenocarcinoma cell against hydrogen peroxide (H2O2)-mediated oxidative stress and oxidativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
0
8
0
2
Order By: Relevance
“…The results corroborate the findings of Marabini et al that erdosteine exert anti-inflammatory and anti-oxidant properties due to the presence of a pharmacologically active sulfhydryl group that has been found to have a free radical scavenging activity. 43 The histopathological results of this study indicated that the irradiated group revealed atrophied glomeruli. Widened Bowman's space and thickened basement membrane were seen.…”
Section: Discussionmentioning
confidence: 54%
“…The results corroborate the findings of Marabini et al that erdosteine exert anti-inflammatory and anti-oxidant properties due to the presence of a pharmacologically active sulfhydryl group that has been found to have a free radical scavenging activity. 43 The histopathological results of this study indicated that the irradiated group revealed atrophied glomeruli. Widened Bowman's space and thickened basement membrane were seen.…”
Section: Discussionmentioning
confidence: 54%
“…Because of these characteristics, ER's activity in many diseases has been the subject of research (18)(19)(20). Erden et al studied the effectiveness of ER's in a pulmonary fi brosis model, using bleomycin in rats, and demonstrated that it prevents neutrophil accumulation with inhibition by inhibiting acute lung injury and fi brosis, lipid peroxidation and chemokine production (6).…”
Section: Discussionmentioning
confidence: 99%
“…Cells are constantly exposed to reactive oxygen species including those metabolically generated as products of aerobic respiration [ 32 , 33 ] and those originated from environmental pollutants [ 34 ]. It has been observed that hydrogen peroxide concentrations above 100 μ M are cytotoxic and genotoxic in A549 cells [ 35 ] causing DNA damage [ 36 ] and inducing the catalytic activities of DNA topoisomerase complexes [ 37 39 ]. Furthermore, the H 2 O 2 -induced damage could be also revealed by the oxidation of DNA bases, for instance, guanine adducts like 8-oxo-7,8-dihydro-2′-deoxyguanosine (8-oxo-dG) [ 40 ].…”
Section: H 2 O 2 Indmentioning
confidence: 99%